2012
DOI: 10.1175/jcli-d-11-00449.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Barents Sea Ice in the Wintertime Cyclone Track and Emergence of a Warm-Arctic Cold-Siberian Anomaly

Abstract: Sea ice variability over the Barents Sea with its resultant atmospheric response has been considered one of the triggers of unexpected downstream climate change. For example, East Asia has experienced several major cold events while the underlying temperature over the Arctic has risen steadily. To understand the influence of sea ice in the Barents Sea on atmospheric circulation during winter from a synoptic perspective, this study evaluated the downstream response in cyclone activities with respect to the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
235
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 322 publications
(257 citation statements)
references
References 32 publications
16
235
4
2
Order By: Relevance
“…Instead, significant correlations occur over parts of the United States and over northern Canada (with NH ice area). The so called "warm Arctic-cold mid-latitude pattern" after low September ice area, which has been reported in several other recent studies (Overland et al 2011;Inoue et al 2012;Petoukhov and Semenov 2010) is not very pronounced in our analysis although low September BAKA ice area is also followed by warm temperatures in the BAKA area itself. One reason for this might be that we use detrended data while many other studies analyzed differences between the last decade with strongly reduced NH ice and the decades before.…”
Section: Air Temperaturesupporting
confidence: 78%
See 1 more Smart Citation
“…Instead, significant correlations occur over parts of the United States and over northern Canada (with NH ice area). The so called "warm Arctic-cold mid-latitude pattern" after low September ice area, which has been reported in several other recent studies (Overland et al 2011;Inoue et al 2012;Petoukhov and Semenov 2010) is not very pronounced in our analysis although low September BAKA ice area is also followed by warm temperatures in the BAKA area itself. One reason for this might be that we use detrended data while many other studies analyzed differences between the last decade with strongly reduced NH ice and the decades before.…”
Section: Air Temperaturesupporting
confidence: 78%
“…According to studies by Alexander et al (2004) and Deser et al (2004), an increased meridional temperature gradient would lead to increased cyclonic activity in order to re-establish the original mass and heat-balances. A recent study by Inoue et al (2012) suggested that the meridional temperature gradient due to ice variations in the Barents Sea is the main reason for the observed SLP anomalies and the connected "warm Arctic-cold continent" temperature patterns in recent years. A number of studies showed predictability of sea ice anomalies up to 6 months and more Tietsche et al 2014;Chevallier and Salas-Mélia 2012;Blanchard-Wrigglesworth et al 2011a, b;) mainly due to persistence, reemergence and advection processes.…”
Section: Meridional Temperature Gradientmentioning
confidence: 99%
“…Another mechanism on shorter timescales leading to negative NAO/AO-like changes and colder surface air temperatures especially over Europe in winter has been discussed by Petoukhov and Semenov (2010) and Inoue et al (2012). Changes in the November sea ice cover in the Barents Sea lead to an additional heat source and intensified cyclones in downstream Arctic regions in the following months.…”
Section: Introductionmentioning
confidence: 99%
“…A composite analysis of the more extreme cases within this group shows the distinctive north-south temperature dipole and intensification of the northern flank of the Siberian high thus creating more cold surges downstream (Inoue et al 2012). However, taken as an ensemble mean, sea-ice do not systematically induce a mid-latitude cooling response as seen in Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…Inoue et al (2012) was one of the first papers to point out this particular anomaly where the warming Arctic and change in seaice concentration over the Barents Sea influence the dominant cyclone migration pathway creating an extension of the Siberian High along the coast of the Eurasian continent leading to a coldair outburst in the mid-latitudes.…”
Section: Introductionmentioning
confidence: 99%